Pyrene‐Thiol‐modified Pd Nanoparticles on Carbon Support: Kinetic Control by Steric Hinderance and Improved Stability by the Catalyst‐Support Interaction. Issue 23 (9th September 2020) - Yoshii, Takeharu; Umemoto, Daiki; Yamamoto, Masanori; Kuwahara, Yasutaka; Nishihara, Hirotomo; Mori, Kohsuke; Kyotani, Takashi; Yamashita, Hiromi
Abstract: Aerobic oxidative dehydrogenation of amines to imines by thiol‐modified Pd nanoparticle (NP) catalysts on carbon supports is reported herein. Whereas conventional non‐modified Pd NP catalysts are nearly inactive, the carbon‐supported Pd catalysts modified with thiol ligands efficiently catalyze the reaction with high selectivity. Kinetic studies and DFT calculations reveal that the rate‐limiting imine product desorption step is significantly boosted on the thiol ligands‐modified Pd surface compared to the non‐modified Pd surface due to the steric hindrance of the ligands. Furthermore, the catalytic activity is dramatically enhanced in the presence of both pyrene‐functionalized thiol modifiers and graphene‐based carbon supports; 96 % conversion is attained after 4 h at 110 °C. The π – π interactions between pyrene groups and the highly crystallized carbon surface suppress the leaching of ligands, which offers improved catalyst stability even under O2 atmosphere at 110 °C, thereby resulting in high activity. Abstract : Unlock hidden catalysis : Pd nanoparticles modified with pyrene‐thiol ligands on carbon supports which act as an efficient and selective catalyst for aerobic oxidative dehydrogenation of amines to imines are reported herein. The rate‐limiting product desorption step is boosted due to the steric hindrance of the ligands, and the ligand leaching is suppressed due to the catalyst‐support π–π interactions, rendering this material an active catalyst.